Recent development in microbial electrochemical technologies: Biofilm formation, regulation, and application in water pollution prevention and control. (October 2022) - Zhou, Lean; Wu, Yongliang; Zhang, Shiqi; Li, Yifu; Gao, Yang; Zhang, Wei; Tian, Liu; Li, Tian; Du, Qing; Sun, Shiquan
Abstract: With the higher requirements of energy conservation and carbon emission reduction, wastewater treatment process is facing unprecedented challenges. Microbial electrochemical technologies (METs) have been gradually applied to wastewater treatment due to their unique ability to convert organic waste into green energy and recover useful byproducts. Here, we comprehensively summarize the recent advances in the following areas: (1) the basis of METs containing different types of electroactive microorganisms and the main extracellular electron transfer (EET) forms; (2) Key factors that affect electroactive biofilm formation and MET performance, such as the electrode potential, external resistance, dissolved oxygen, microbial inoculation source, chemical signaling, electrode materials, and substrates for wastewater treatment processes; (3) The application of METs in energy recovery synchronized with wastewater treatment, high value-added by-product recovery, heavy metal reduction, biological early warning and nutrient recovery. Finally, we summarize and discuss the future development directions of METs. Highlights: The species of EABs and the electron transfer mechanism are summarized. Factors affecting EABs formation and MET performance are summarized. Waste treatment, resource recovery and biosensors are main application of EABs. The chemical conversion efficiency is a limiting factor in EAB application.